The comparison between fixed versus degressive doses of medroxyprogesterone acetate combined with letrozole in patients of progestin-primed ovarian stimulation protocol: a propensity score-matched study - Zhang, Ying; Li, Hao; Zhu, Shanshan; Jiang, Shengfang; Zhao, Wenxian; Wang, Xiaoning; Tian, Liu; Zhao, Guangming; He, Nongqiao; Diao, Honglu; Cao, Hong; Zhang, Changjun (Frontiers in Endocrinology, 2023)
Objective: To explore the cycle characteristics and pregnancy outcomes of progestin-primed ovarian stimulation (PPOS) using fixed versus degressive doses of medroxyprogesterone acetate (MPA) in conjunction with letrozole (LE) in infertile women by propensity score matching (PSM) analysis. Population: A total of 3173 infertile women undergoing their first in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatment within the period from January 2017 to December 2020. Methods: A total of 1068 and 783 patients who underwent a fixed dose of MPA combined with LE and a degressive dose of MPA combined with LE protocols, respectively, were enrolled in this study. The freeze-all approach and later frozen-thawed embryo transfer (FET) were performed in both groups. Propensity score matching (1:1) was performed. Results: We created a perfect match of 478 patients in each group. The dosage of MPA, the LH serum level on the eighth day of stimulation, progesterone (P) level and LH level on the hCG trigger day were significantly higher in the LE + fixed MPA group than in the LE + degressive MPA group (52.1 ± 13.1 mg vs. 44.9 ± 12.5 mg; 5.0 ± 2.7 IU/L vs. 3.7 ± 1.7 IU/L; 0.9 ± 0.5 ng/ml vs. 0.8 ± 0.5 ng/ml; 3.3 ± 2.4 IU/L vs. 2.8 ± 1.9 IU/L; P < 0.01). The duration of Gn, the number of follicles with diameter more than 16 mm on trigger day, the estradiol (E2) level on the hCG trigger day were lower in the LE + fixed MPA group than in the LE + degressive MPA group (9.7 ± 1.7 days vs. 10.3 ± 1.5 days; 5.6 ± 3.0 vs. 6.3 ± 3.0; 1752.5 ± 1120.8 pg/ml vs. 1997.2 ± 1108.5 pg/ml; P < 0.001). No significant difference was found in the incidence of premature LH surge, the number of oocytes retrieved, the number of top-quality embryos, clinical pregnancy rate (CPR), CLBR or fetal malformation rate between the two groups. Conclusions: The combination of a degressive MPA dose with LE proved effective in reducing the total MPA dosage with comparable premature LH surge and pregnancy outcomes in women undergoing the PPOS protocol.